(untitled) (Swiss Medical Weekly, 2024)
Temporary, sudden, shooting and recurrent unilateral facial pain in the supply area of one or more trigeminal nerve branches characterises trigeminal neuralgia. Innocuous stimuli trigger the pain, e.g. chewing, speaking or brushing teeth. In some patients, paroxysms superimpose on continuous pain. In aetiological terms, idiopathic, classic (due to neurovascular compression) and secondary trigeminal neuralgia (e.g. due to multiple sclerosis, brainstem ischaemia and space-occupying lesions) are defined. Many drugs may be efficacious, with carbamazepine being first-choice therapy. However, non-pharmacological and invasive procedures may also help. To reach the correct diagnosis and determine the best therapeutic measures, adequate pain characterisation and interdisciplinary collaboration are essential. We hereby present our experience of an interdisciplinary approach for the diagnosis and treatment of trigeminal neuralgia.